2012
DOI: 10.1183/09031936.00068411
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfumarate inhibits CXCL10 via haem oxygenase-1 in airway smooth muscle

Abstract: CXCL10 stimulates mast cell infiltration into airway smooth muscle bundles and, thus, activate cytokine secretion and airway smooth muscle cell (ASMC) proliferation. Dimethylfumarate (DMF) reduces cytokine secretion by lymphocytes and ASMC proliferation through haem oxygenase (HO)-1. Therefore, we investigated the potency of DMF to inhibit tumour necrosis factor (TNF)-a-and interferon (IFN)-c-induced CXCL10 secretion by human ASMCs.Human primary ASMCs were pre-incubated with DMF and/or fluticasone and/or gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…The mechanism underlying the decrease in macrophage infiltration observed in glomeruli of anti-GBM Ab-treated GEC HO-1 rats is unknown. In this regard, it was previously reported that GEC can attract macrophages through the production and secretion of chemokines, as shown for the chemokine CXCL10 [31], while HO-1 negatively regulates CXCL10 [32]. …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the decrease in macrophage infiltration observed in glomeruli of anti-GBM Ab-treated GEC HO-1 rats is unknown. In this regard, it was previously reported that GEC can attract macrophages through the production and secretion of chemokines, as shown for the chemokine CXCL10 [31], while HO-1 negatively regulates CXCL10 [32]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, CXCL10 secretion by ASMC is sensitive to changes in cellular glutathione (GSH) levels [27], suggesting a link of this signaling pathway to the asthma-associated upregulation of mitochondria, which control the cellular redox system [42]. Interestingly, the thiazolidinedione ciglitazone strongly inhibited cytokine-induced CXCL10 protein without affecting CXCL10 mRNA level, suggesting that CXCL10 is regulated on the posttranslational level in ASMC [41].…”
Section: Cxcl10 (Ip-10)mentioning
confidence: 99%
“…NF- κ B activity was reported to be increased in the airways of asthmatic patients [97]. In addition, proinflammatory cytokines such as TNF- α activated NF- κ B in ASMC in vitro , which resulted in the secretion of a variety of proinflammatory factors including RANTES, CXCL10, or CCL11 [26, 27, 35]. In vitro, inhibition of NF- κ B downregulated the release of a range of proinflammatory mediators by ASMC [98].…”
Section: Dmf As a Potential Asthma Therapymentioning
confidence: 99%
See 2 more Smart Citations